Grammatical Differences Between African American Vernacular English (AAVE) And Standard English (SE) in Black English Vocabulary by Teacher Rodrigo Honorato Youtube Video - Arijie Balqiis Suryanjani; Ujang Suyatman; Irman Nurhapitudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research examines the grammatical differences and characteristics of grammatical between African American Vernacular English (AAVE) and Standard English (SE). This research uses a descriptive qualitative approach. The researcher collected data by selecting 10 videos from the Black English vocabolary playlist, in Teacher Rodrigo Honorato's youtube account. The data obtained will be collected and then analyzed based on grammatical differences and grammatical characteristics. The results of this study show that there are many differences between AAVE and SE languages including in grammatical aspects. AAVE and SE also have different characteristics. These differences are not a big problem for native speakers, but can be confusing for foreign speakers because they are not in accordance with the language rules commonly known by ordinary people.